Implementasi Pendekatan Konstruktivisme melalui Model Pembelajaran CLIS (Children Learning In Science) dan Pengaruhnya terhadap Aktivitas Belajar dan Kemampuan Kognitif Siswa - Dewi Ratnasari; Sukarmin Sukarmin; Y. Radiyono (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2017)
Abstract The aim of this research is to implementation constructivism approach through CLIS (Children Learning In Science) learning model and its immpact toward students’ learning activities and cognitive ability. This action resesarch was analyzed by descriptive quantitative. Research subjects is students in 11th grade in the academic year 2013/2014 in the static fluid material. The data of this research from observation technique when learning process and cognitive test in the end of learning. Students’ learning activities in this research consist of visual activities, oral activities dan writing activities that described into many indicators, whereas cognitive test uses multiple choice instrument that has been properness analyzed. Based on research result and data analysis get result as follows: 1) The value of normalization in visual activities is 0,78 (high), oral activities is 0,31 (adequate), writing activities is 0,49 (adequate); 2) The increase of average achievement of students’ cognitive ability based on gain normalization is 0,32 (adequate) after learning with constructivism approach through CLIS (Children Learning In Science) model. Keywords: learning activities, Children Learning In Science, cognitive ability. Abstrak Penelitian ini bertujuan untuk mengimplemantasikan pendekatan konstruktivisme melalui model pembelajaran CLIS (Children Learning In Science) dan pengaruhnya terhadap aktivitas belajar dan kemampuan kognitif siswa. Penelitian tindakan ini dianalisis menggunakan deskriptif kuantitatif dengan subjek penelitian adalah siswa kelas XI pada tahun ajaran 2013/2014 pada materi fluida statis. Data penelitian diperoleh dari hasil observasi selama proses pembelajaran dan hasil tes kognitif pada akhir pembelajaran. Aktivitas belajar siswa pada penelitian ini terdiri dari visual activities, oral activities dan writing activities yang dijabarkan menjadi beberapa indikator, sedangkan tes kognitif siswa menggunakan instrumen pilihan ganda yang telah dianalisis kelayakannya. Berdasarkan hasil penelitian dan analisis data diperoleh hasil sebagai berikut: 1) Nilai gain ternormalisasi pada visual activities sebesar 0,78 (tinggi); oral activities sebesar 0,31 (sedang); writing activities sebesar 0,49 (sedang); 2) Peningkatan rata-rata nilai ketuntasan kemampuan kognitif siswa berdasarkan nilai gain ternormalisasi sebesar 0,32 (sedang) setelah pembelajaran dengan mengimplementasi pendekatan konstruktivisme melalui model CLIS (Children Learning In Science). Kata-kata Kunci: Aktivitas belajar, Children Learning In Science, kemampuan kognitif.